Denaturalization of bankruptcy procedures: payments of bankruptcy credits out of bankruptcy - Barboza Flores, Juan Ramón (2024)
This article addresses the problem noted in the Peruvian Bankruptcy Law: the bankruptcy authority has been unable to neutralize payments of bankruptcy credits made outside the rules of bankruptcy. We are faced with the need for debtors to continue with business activity, to generate greater wealth and not increase the crisis they are going through, while we are faced with the possible denaturalization of the bankruptcy procedures. To address this problem, the author will propose the implementation of a regime of action that allows the balance between the need for payments and the bankruptcy procedure.